Written mathematical communication skills in solving set theory problems: A descriptive study of preservice elementary teachers - Najwa Mahadini; Octavian Muning Sayekti; Asih Mardati (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2025)
This study examined the written mathematical communication skills of preservice elementary teacher education students in solving problems related to set theory. A descriptive qualitative approach was employed with 28 first-semester students at a private university in Yogyakarta as subjects. Using a written essay test, with three set theory questions, data were gathered. These questions were designed to cover four aspects of mathematical communication: figuring out the problem, turning it into a mathematical model, working it out, and coming to a conclusion. The results showed clear variations in student performance. The majority of students were in the high-skill category (43%), followed by the moderate category (36%) and the low category (21%). Students in the high category fulfilled almost all indicators well, whereas those in the moderate category often made mistakes in mathematical modeling and conclusion writing. Meanwhile, students in the low category struggled from the initial problem comprehension stage through to formulating a conclusion. Overall, although a considerable number of students exhibited high-level skills, the findings suggest that written mathematical communication skills among preservice elementary teachers are not yet evenly developed. More than half of the students fell into the moderate and low categories, indicating a need for improvement, particularly in careful problem interpretation, accurate mathematical modeling, and the organization of solution steps into a clear and coherent written form.